Relationship between Internal Market Freedoms and Fundamental Rights in the Jurisprudence of the Court of Justice of the European Union - Jarukaitis, Irmantas (Teisė, 2022)
This paper examines the relationship between internal market freedoms and fundamental rights protection in the European Union law. It analyzes the jurisprudence of the Court of Justice of the European Union developed before the Lisbon Treaty and changes predetermined by the entry into force of the Charter of Fundamental Rights of the European Union.
Keywords: internal market freedoms; protection of fundamental rights; relationship; Charter of Fundamental Rights of the European Union; freedom to conduct business; evolution of jurisprudence of the Court of Justice of the European Union